On the street where you live - Clark, Mary Higgins; Simon and Schuster (London : Simpn andSchuster, 2001)
Feeling a need for stability after her divorce and pursuit by a stalker, criminal defense attorney Emily Graham accepts a job with a Manhattan law firm and buys the former family house in New Jersey. When the house is renovated, the corpse of a missing woman turns up along with evidence linked to a family disappearance in 1892.
Publisher's Weekly.
Wilson's Fiction.
Wilson's Senior High School.
Adult
English
Keywords: Dwellings -- New Jersey -- Fiction; Families -- Fiction; Murder -- Fiction; Women lawyers -- New York (State) -- New York -- Fiction; Family life -- Fiction; Homicide -- Fiction; Houses -- New Jersey -- Fiction; Mystery fiction; Women lawyers -- Fiction; New Jersey -- Fiction; New York (N.Y.) -- Fiction; New Jersey -- Fiction; New York (N.Y.) -- Fiction